2001
DOI: 10.1002/eat.1088
|View full text |Cite
|
Sign up to set email alerts
|

Serum beta‐carotene in anorexia nervosa patients: A case‐control study

Abstract: Hypercarotenemia is a common finding in AN patients, especially in the restricter subgroup. The high prevalence of elevated serum betaC in AN patients supports its diagnostic value in atypical forms of eating disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 19 publications
0
16
1
1
Order By: Relevance
“…Other studies have found that a-carotene levels were significantly higher in patients with a greater degree of eating pathology (Rock, Gorenflo, Drewnowski, & Demitrac, 1996). The percentage of subjects with high b-carotene levels was lower than in other studies (Boland et al, 2001), although in our country, mean serum values of carotenes are lower than in other Caucasian populations (Olmedilla, Granado, Gil-Martinez, Blanco, & Rojas-Hidalgo, 1997).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Other studies have found that a-carotene levels were significantly higher in patients with a greater degree of eating pathology (Rock, Gorenflo, Drewnowski, & Demitrac, 1996). The percentage of subjects with high b-carotene levels was lower than in other studies (Boland et al, 2001), although in our country, mean serum values of carotenes are lower than in other Caucasian populations (Olmedilla, Granado, Gil-Martinez, Blanco, & Rojas-Hidalgo, 1997).…”
Section: Discussioncontrasting
confidence: 60%
“…A thiamin deficit was found in 19% of a sample of adult anorexics (Winston, Jamieson, Madira, Gatward, & Palmer, 2000), and it is common to find high carotene concentrations (Boland, Beguin, Zech, Desager, & Lambert, 2001;Curran-Celentano, Erdman, Nelson, & Grater, 1985). Nevertheless, many of these studies were carried out with adult anorexics with a long duration of the disorder and it is not clear whether young adolescents, in whom the evolution time of the disorder is shorter, present marked biochemical and nutritional deficiencies.…”
Section: Introductionmentioning
confidence: 92%
“…21 It tends to be more common in the restricting subtype of this disease, and is associated with numerous other dermatologic manifestations, such as brittle hair and nails, lanugo-like body hair, and xerosis. 22,23 Although Alzheimer's disease has been associated with carotenoderma in some reports, most studies on serum carotenoids in these patients show that their levels of carotenoids and retinol are depressed, and may be associated with the development of dementia. 24,25 A true association between Alzheimer's disease and carotenoderma is unclear at this time.…”
Section: Carotenodermamentioning
confidence: 98%
“…Boland et al 40 encontraram em amostra de 101 pacientes com AN, prevalência de 62,0% de hipercarotenemia. Sherman et al 41 observaram prevalência menor em sua amostra, apenas 13,0% dos portadores de TA apresentavam esse quadro, nenhum deles com BN.…”
Section: I S C U S S ã Ounclassified